Project Delft (OverHolland, 2008)
This project for the Delft rail zone was designed by AWG architects for the Delft University of Technology within the scope of the research project 5x5 Projects for the Dutch city. The study on the potential of the area that will be freed up when the rail is placed underground is an academic exercise just like the studies for the other Dutch cities of the 5x5 project. It has to be seen as separate from the practical assignments that are currently being worked on in Delft.